Transformasi Digital Melalui Aplikasi Signal dalam Meningkatkan Pelayanan Pajak Kendaraan di Kabupaten Bojonegoro - Eriyanti Putri Anggraeni; Esa Septian; Junadi junadi (PERSPEKTIF, 2026)
This study aims to analyze the digital transformation of motor vehicle tax services through the use of the SIGNAL (National Digital Samsat) application in Bojonegoro Regency. The study uses a qualitative approach with a case study method through interviews, observations, and documentation of eight informants consisting of Samsat officers, police, and application users. Data analysis was conducted using the Technology Acceptance Model (TAM) framework, taking into account social dimensions, public policy, and institutional readiness. The results show that the SIGNAL application provides benefits in the form of time efficiency, ease of access, and increased service transparency. However, its use still faces technical obstacles, low digital literacy, and limited user socialization and assistance. This study confirms that the success of digital transformation in public services is not only determined by the quality of technology, but also by institutional support and sustainable policy implementation. Theoretically, this study expands the application of TAM in the context of public services by incorporating social and institutional aspects.